Sintesis Komposit Fe3O4/Hidroksiapatit Menggunakan Metode Kopresipitasi Dengan Variasi Suhu Sintering Dan Penambahan Fe3O4 - Dion Julio Iskandar; Ahmad Fadli; Idral Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Magnetite/Hydroxyapatite composite is one of the media as drug carrier for a drug delivery system. The purpose of this research is synthesis of the composite, and analysing the effect of percentage of Fe and sintering temperature to the characteristic of the composite. The powder of magnetite was dispersed in 100 ml of aquadest and mixed with 33,7 mmol Ca(NO3)2.4H2O for 15 minutes, and 20 mmol (NH4)2HPO4 added to the suspense. The pH of suspension was controlled by added NH4OH 25% until pH 11 and left for reacting for 120 minutes at 90ºC. The suspension was aged for 1 day, washed and then the precipitate was separated from the suspense. The precipitate was dried for 1 day at 90ºC and ended with sintering the precipitate for 2 hours at variable temperature until powder of composite was collected. The powder of composite was characterized with XRD, VSM and FESEM. The increase of sintering temperature from 400ºC to 800ºC affecting the sample crystallinity from 14,22% to 22,55% and the magnetic saturation value from 17,2 emu/g to 4,0 emu/g. Based on the resulted from characterized of the composite, concluded that the synthesis of composite magnetite/hydroxyapatite were succeeded.Keywords :drug carrier, hydroxyapatite, composite, magnetite, coprecipitation